A Manual on Statistics of International Trade in Services. (Manuals and Guides, 2003)
The Manual sets out an internationally agreed framework for the compilation and reporting of statistics on international trade in services in the broad sense. It addresses the growing need, including in international trade negotiations and agreements, for more detailed, comparable, and comprehensive statistics on this type of trade in its various forms. The recommendations will enable countries to progressively expand and structure the information they compile in an internationally comparable way. The Manual conforms with and explicitly relates to the System of National Accounts 1993 and the fifth edition of the IMF's Balance of Payments Manual. It is published jointly by the United Nations, European Union, IMF, OECD, UNCTAD, and World Trade Organization.